Teaching Business Law to Non-Law Students, Culturally and Linguistically Diverse (‘CaLD’) Students, and Large Classes - Kariyawasam, Kanchana; Low, Hang Yen (Journal of University Teaching and Learning Practice, 2014)
This paper is largely based on the experience of teaching law to students with non-legal background in business schools, with a focus on internationalisation and the large class lecture format. Business schools often consist of large classes which include a significant proportion of Culturally and Linguistically Diverse (CaLD) students. Teaching a difficult and demanding subject to a large cohort of students from increasingly diverse backgrounds can be an onerous task. The existence of these conditions present different teaching challenges and requires a re-examination of teachers’ approaches to student learning. In this article, the experience of teaching law in business schools is approached through an examination of the challenges and problems arising from (a) teaching law to non-law students (b) teaching CaLD students (c) teaching large classes. At each stage, the writers explore effective solutions and strategies to deal with these issues.